The Role of Productivity, Transportation Costs, and Barriers to Intersectoral Mobility in Structural Transformation - Karayalcin, Cem (IMF Working Papers; Working Paper ;, 2015)
The process of economic development is characterized by substantial reallocations of resources across sectors. In this paper, we construct a multi-sector model in which there are barriers to the movement of labor from low-productivity traditional agriculture to modern sectors. With the barrier in place, we show that improvements in productivity in modern sectors (including agriculture) or reductions in transportation costs may lead to a rise in agricultural employment and through terms-oftrade effects may harm subsistence farmers if the traditional subsistence sector is larger than a critical level. This suggests that policy advice based on the earlier literature needs to be revised. Reducing barriers to mobility (through reductions in the cost of skill acquisition and institutional changes) and improving the productivity of subsistence farmers needs to precede policies designed to increase the productivity of modern sectors or decrease transportation costs.